2018
DOI: 10.1161/circep.117.005258
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Sites Where Persistent Atrial Fibrillation Is Terminated by Localized Ablation

Abstract: BACKGROUND:The mechanisms by which persistent atrial fibrillation (AF) terminates via localized ablation are not well understood. To address the hypothesis that sites where localized ablation terminates persistent AF have characteristics identifiable with activation mapping during AF, we systematically examined activation patterns acquired only in cases of unequivocal termination by ablation. METHODS AND RESULTS:We recruited 57 patients with persistent AF undergoing ablation, in whom localized ablation termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 51 publications
(70 reference statements)
4
40
0
Order By: Relevance
“…Baseline maps showed that all patients had both rotational and focal PDs which were intermittent and repetitive in localized regions. This is in keeping with prior studies with this noninvasive mapping system, 7,8 and is also compatible with studies using basket catheters for contact mapping 3,4,9,10,16 . Studies utilizing the ECGI system have described a greater number of drivers per patient than studies using analysis of contact electrograms from basket catheters.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Baseline maps showed that all patients had both rotational and focal PDs which were intermittent and repetitive in localized regions. This is in keeping with prior studies with this noninvasive mapping system, 7,8 and is also compatible with studies using basket catheters for contact mapping 3,4,9,10,16 . Studies utilizing the ECGI system have described a greater number of drivers per patient than studies using analysis of contact electrograms from basket catheters.…”
Section: Discussionsupporting
confidence: 76%
“…Mapping data suggest that mechanisms supporting AF are patient specific in terms of the location and characteristics of drivers and that these mechanisms evolve over time with remodeling in terms of the number and distribution of drivers 3,4,6‐10 . Despite this, for reasons that remain unclear, PVI remains a relatively effective treatment for persistent AF, particularly when AF terminates during PVI 1,2,11 …”
Section: Introductionmentioning
confidence: 99%
“…Similar to this study, we identified repetitive activation patterns in all patients with persistent AF at sites where AF terminated with limited ablation, using electrograms obtained from basket catheters, highly suggestive of mechanistic importance of these sites (Figure ) . The validity of these approaches is further supported by other mapping methods that show repetitive patterns using noncontact methods or using the same mapping catheter and show stability of spatiotemporal dispersion .…”
supporting
confidence: 80%
“…Of note, the smaller area of the Pentaray (cartoon in blue) and necessary overlapping of these in Wolf et al may be responsible for the higher number of focal activations. Adapted with permission from Zaman et al…”
mentioning
confidence: 99%
“…Better understanding of how PVI affects persistent AF may offer insight to improve technique, guide patient selection, or target alternative mechanisms. Complexity in AF likely reflects a network of competing mechanisms including multiple spatially non‐localized wavelets, 4,5 spatially localized fibrillatory drivers, 6,7 or ganglionated plexuses (GPs) 8 . PVI acts locally by electrically isolating the PVs but may also lead to spatially distributed effects by disarticulating nonlocal mechanisms such as autonomic activity driven by GPs 9 .…”
mentioning
confidence: 99%